2023
DOI: 10.3390/polym15071597
|View full text |Cite
|
Sign up to set email alerts
|

Towards Electrochemical Sensor Based on Molecularly Imprinted Polypyrrole for the Detection of Bacteria—Listeria monocytogenes

Abstract: Detecting bacteria—Listeria monocytogenes—is an essential healthcare and food industry issue. The objective of the current study was to apply platinum (Pt) and screen-printed carbon (SPCE) electrodes modified by molecularly imprinted polymer (MIP) in the design of an electrochemical sensor for the detection of Listeria monocytogenes. A sequence of potential pulses was used to perform the electrochemical deposition of the non-imprinted polypyrrole (NIP-Ppy) layer and Listeria monocytogenes-imprinted polypyrrole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Liustrovaite et al [ 134 ] found that an SPCE electrode is more efficient than a Pt electrode for L. monocytogenes bacteria (0.5–2 μm-long) ( Figure 9 ) detection resulting in a LOD of 70 CFU/mL. Since template extraction is challenging for MIP-based sensors, various extraction solutions (sulfuric acid, acetic acid, L-lysine, and trypsin) were tested.…”
Section: Mip Application For the Detection Of Biomarkers Of Infectiou...mentioning
confidence: 99%
See 1 more Smart Citation
“…Liustrovaite et al [ 134 ] found that an SPCE electrode is more efficient than a Pt electrode for L. monocytogenes bacteria (0.5–2 μm-long) ( Figure 9 ) detection resulting in a LOD of 70 CFU/mL. Since template extraction is challenging for MIP-based sensors, various extraction solutions (sulfuric acid, acetic acid, L-lysine, and trypsin) were tested.…”
Section: Mip Application For the Detection Of Biomarkers Of Infectiou...mentioning
confidence: 99%
“… Schematic representation of platinum electrode or SPCE modification with L. monocytogenes bacteria imprinted Ppy [ 134 ]. …”
Section: Figurementioning
confidence: 99%
“…Another approach to obtaining sensors with high specificity is the creation of molecular imprinted polymers (MIPs). MIPs are polymer-based artificial receptors with the ability to recognize different types of target molecules such as amino acids, peptides [97], pesticides [98], drugs [99], and even larger molecules such as proteins [100] and whole cells [101]. The target molecules act as a template and interact with functional monomers to form a complex during polymerization, and then the template can be removed, leaving cavities able to rebind the template molecules thanks to its geometry and chemical moieties.…”
Section: Nanomaterials In Electrochemicalmentioning
confidence: 99%